The Changes in Coral Reef Area on Semujur Island, Central Bangka - Sandri; Okto Supratman; M. Rizza Muftiadi (Yayasan Serumpun Karang Konservasi, 2024)
Semujur Island, located in Kebintik Village, Pangkalan Baru Subdistrict, Central Bangka Regency, covers an area of approximately 40 hectares and is home to 47 households, the majority of whom are fishermen. The island is known as a center for fishing activities and grouper cultivation and has potential for marine tourism through its diverse coral reefs and reef fish. This study aimed to analyze changes in coral reef area using Sentinel-2A satellite imagery and to assess the influence of sea surface temperature on these changes. Ground truth data were collected in March 2023, consisting of 60 samples classified into four categories: coral reef, dead coral, seagrass, and sand. Image analysis included sunglint correction, water column correction, and supervised classification using the Maximum Likelihood Classifier method. The results indicated a decrease in coral reef area from 104.61 hectares in 2016 to 99.91 hectares in 2023, representing a reduction of approximately 4.5%. Analysis of sea surface temperature data showed an increasing trend, contributing to coral reef degradation. These findings highlight the urgent need for sustainable management efforts to protect the coral reef ecosystem of Semujur Island.